Penerapan Konsep Dasar Pemikiran Al-Ghazali dalam Pendidikan Agama Islam - Rahma, Renita Nur; Amda, Ahmad Dibul; Baryanto, Baryanto; Deriwanto, Deriwanto; Karolina, Asri (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This study aims to determine the basic concepts of Al-Ghazali's thought in Islamic education. This study uses a qualitative approach with the type of library research. The data collection technique used in this research is documentation. Data collection refers to books or books that have something to do with the concept of Islamic religious education according to Al-Ghazali. Researchers use content analysis as a reference in extracting information. The results of the study, the basic concept of Al-Ghazali's thought in Islamic Religious Education includes educational factors, namely aqidah education, moral education, and shari'ah education. Then the application of the basic concepts of Al-Ghazali's thoughts in Islamic religious education from the material and methods. Aqidah educational material, namely about the substance of Allah, prophethood, and death. Meanwhile, the methods are memorizing, teaching, and monitoring. Then the material moral education is morals towards Allah, morals of parents, morals of oneself, and morals towards others. The method is self-improvement, self-development, kufin. Then the shari'ah education material is ushul, furu, and muqodimat, the methods are through the talqin method, riyadho mujahadah, kalam jadal, and bit talathuf da'wah. In conclusion, there are three factors in the application of the concept of Al-Ghazali's thought in Islamic education, namely the factor of Aqidah Education, Moral Education, and Sharia Education. Keywords: Concept Application, Al-Ghazali Thought, Islamic Education Learning.